2015
DOI: 10.1021/acs.orglett.5b01046
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)/(III)-Catalyzed Synthesis of Cyclic Ethers; Valency-Controlled Cyclization Modes

Abstract: Strategic use of oxophilic (hard) gold(III) and π-philic (soft) gold(I) catalysts provides access to two types of cyclic ethers from propargylic alcohols. Thus, heating propargylic alcohols with an oxophilic gold(III) catalyst (AuBr3) results in cyclization to afford cyclic ethers bearing an acetylenic moiety, due to coordination of gold(III) to the oxygen of the propargylic hydroxyl group. On the other hand, propargylic alcohols with a π-philic gold(I) catalyst (Ph3PAuNTf2) induces Meyer-Schuster rearrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 42 publications
0
26
2
Order By: Relevance
“…In particular, gold complexes with their operationally simple, safe and neutral reaction conditions, had widely contributed to the development of new glycosylation methods. Gold(I) and gold(III) complexes are usually alkynophilic [ 2 ], carbophilic and oxophilic because of their affinity towards the alkynes’ and C–O π systems [ 3 6 ]. Thus, various research groups employed either a remote alkyne group possessing versatile glycosyl donors [ 7 16 ] or used glycals [ 17 ] for effective O -, C -, and S -glycosylation reactions using gold(I) and gold(III) catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, gold complexes with their operationally simple, safe and neutral reaction conditions, had widely contributed to the development of new glycosylation methods. Gold(I) and gold(III) complexes are usually alkynophilic [ 2 ], carbophilic and oxophilic because of their affinity towards the alkynes’ and C–O π systems [ 3 6 ]. Thus, various research groups employed either a remote alkyne group possessing versatile glycosyl donors [ 7 16 ] or used glycals [ 17 ] for effective O -, C -, and S -glycosylation reactions using gold(I) and gold(III) catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, among many other types of heterogeneous catalysts, the last two decades have seen an impressive number of examples showing the activity, and especially the selectivity of gold and copper in many catalytic reactions. For the particular case of the Michael addition, the reported studies indicated that the selectivity can be controlled by tuning the oxidation state of Au from 0 to (I) and (III) . Au support, consisting of an organic functionalized material or an oxide, should play the role controlling the charge density on the Au nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…Alcohols have also proven to be suitable reagents towards the synthesis of the cyclic ether products, in the presence of palladium and gold catalysts [43][44][45][46]. Diastereoselective zinc-catalyzed alkynylation of α-bromo oxocarbenium ions to synthesize trans-α-alkynyl-β-halo pyran and furan derivatives is known [47].…”
Section: Introductionmentioning
confidence: 99%